Penelitian pembuatan kompon karet untuk sol dan foxing sepatu kanvas - Emiliana Kasmudjiastuti (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1992)
Exsperiments of making rubber compound for canvas shoe sole and foxing have been done by varying filler (MgCO3). Composition used for rubber compound is : pale crepe 100 parts; MgCO3 30 parts; CaCO3 75 parts; ZnO 10 parts; stearic acid 0,5 part; napthenic oil 2 parts; paraffin wax 0,5 part; titanium dioxide 10 parts ; AOSP 1 part; MBT 0,4 part; TMT 0,2 part and sulfur 2 parts. The products are 9 kinds of rubber compound and has been tested for physical properties. The physical tests consist of : tensile strength, elongation at break, permanent set, tear strength, elongation at break, permanent set, tear strength, hardness, density, abrassion and flexing. By evaluating their physical properties, the rubber compound for shoe sole and foxing containing 30 parts of MgCO3 and 75 parts of CaCO3 achieving the optimal degree and is in accordance with the Indonesian Industrial Standard for General Purpose of Canvas Shoe (SII.140785). INTISARI Pembuatan kompon karet untuk sol dan foxing sepatu kanvas dengan kandungan bahan pengisi (MgCO3 dan CaCO3) menggunakan formula : pale crepe 100 bagian; MgCO3 30 bagian; CaCO3 75 bagian; ZnO 10 bagian, asam stearat 0,5 bagian; napthenic oil 2 bagian; paraffin wax 0,5 bagian; titanium dioxide 10 bagian; AOSP 1 bagian; MBT 0,4 bagian; MBTS 0,4 bagian; TMT 0,2 bagian dan belerang 2 bagian. Hasil kompon berbentuk lembaran (slab) sebanyak 9 macam diuji sifat fisinya meliputi : tegangan putus, perpanjangan putus, perpanjangan tetap, ketahanan sobek, kekerasan, bobot jenis, ketahanan retak lentur. Dari evaluasi terhadap hasil uji fisis diperoleh kesimpulan bahwa kompon karet untuk sol dan foxing sepatu kanvas dengan kombinasi kandungan MgCO3 30 bagian, CaCO3 75 bagian mempunyai sifat fisis optimum dan memenuhi SII. 1407-85, Sepatu Kanvas Untuk Umum.